Parent and Peer Attachments in Adolescence and Paternal Postpartum Mental Health: Findings From the ATP Generation 3 Study - Macdonald, Jacqui A.; Greenwood, Christopher J.; Letcher, Primrose; Spry, Elizabeth A.; Mansour, Kayla; McIntosh, Jennifer E.; Thomson, Kimberly C.; Deane, Camille; Biden, Ebony J.; Edwards, Ben; Hutchinson, Delyse; Cleary, Joyce; et al. (Frontiers in Psychology, 2021)
Background: When adolescent boys experience close, secure relationships with their parents and peers, the implications are potentially far reaching, including lower levels of mental health problems in adolescence and young adulthood. Here we use rare prospective intergenerational data to extend our understanding of the impact of adolescent attachments on subsequent postpartum mental health problems in early fatherhood. Methods: At age 17-18 years, we used an abbreviated Inventory of Parent and Peer Attachment to assess trust, communication and alienation reported by 270 male participants in their relationships with mothers, fathers and peers. More than a decade later, we assessed the adult males, now fathers, at 12 months postpartum (N = 409 infant offspring) for symptoms of depression, anxiety and stress. Logistic regression was used to examine the extent to which attachment dimensions predicted paternal postpartum mental health, adjusting for potential confounding, and with assessment for interactions between parent and peer attachments. Results: Trust in mothers and peers, and good communication with fathers during adolescence, were associated with 5 to 7 percentage point reductions in postpartum mental health symptoms in early fatherhood. Weak evidence of parent-peer interactions suggested secure attachments with either parent or peer may compensate for an insecure attachment with the other. Conclusions: Our results suggest that fostering trust and communication in relationships that adolescent boys have with parents and peers may have substantial effects on rates of paternal postpartum mental health problems. The protective benefits may be preventative in intergenerational cycles of risk for mental health problems.